(untitled) (Journal of the College of Basic Education, 2022)
Fabric designs have been characterized by continuous development, as the research (Aesthetics of Heritage Forms in Designs of Women’s Fabrics) has accomplished many new concepts and ideas that have opened the way for the multiplicity of design trends for fabrics, being one of the important design techniques with its ability to have many connotations and it is a product that is inspired by the process of building relationships Structuralism. Which are the components and motives that can be relied upon in the designs of fabrics. The research problem has been identified in (Can traditional shapes be employed in the designs of women’s fabrics?). The research aims to reveal the aesthetics of traditional forms and their role in designing women’s fabrics and to present a design proposal for women’s cloth. The importance of the research lies in increasing the intellectual awareness of textile and fashion designers to develop knowledge of the methods and trends that contributed to achieving the aesthetics of the figure. As for the boundaries of the research, it included the objective boundaries: a study Fabric designs that carry heritage shapes and spatial boundaries: The designs of multi-origin women’s fabrics available in the local markets of Baghdad. And temporal boundaries: the product of the fabric designs within the period 2019-2020 AD, which is the period in which the research was completed. As for the second topic, the theoretical framework included three topics, first: the aesthetics of traditional forms in the designs of women’s fabrics Second: the aesthetic dimension of the design form. Third: the technique and its methods in the designs of women’s fabrics, while the third topic dealt with the research procedures that included the method of research and the method of description Analytical, which is most appropriate with the trends of the current research, and among the most important results that came out of the research are the following: 1- Most of the researched designs achieved the adoption of the morphological features to achieve the aesthetics of the heritage shapes and to create various formal effects that were reflected on the movement and distribution of the vocabulary and its trends. The most important thing dealt with in the theoretical framework is the aesthetics of the heritage shapes in the designs of women’s fabrics, 2- “Technology and its methods in designing women’s fabrics achieved the aesthetic and functional dimension of the cloth through the effectiveness of organizing and arranging the vocabulary within the design component. What confirms that the organizational structure depends on the relationships of distribution and arrangement of elements and formations in an interconnected building that works to determine the visual axes with which the recipient perceives the design work, formed on the basis of diversity and exchange between design elements and components, adding aesthetic values ​​to the design component, achieving the attractiveness of the fabric. Recommendations and a list of sources with a summary in Arabic and EnglishIntroduction: The feeling of beauty remained one of the general qualities that characterize human beings, as it is the gift of God (the Almighty) to man, being the only being who possesses the ability to sense and taste beauty, being the supreme absolute value and arising in our souls at every moment through our vision of many things in reality Human life and daily activities, such as contemplation of nature, and we see that the feeling of beauty and its taste does not stop at the borders of the world of matter, but goes beyond it to the world of thought and art. The designs of women’s fabrics are subject to and are clearly affected by the social and economic environment and the development in the technical field, which formed motives that gave the designer the ability to devise and invent new systems and relationships. Resulting from his self-sensitivity to the components from which he derives the design idea, besides Its cultural and philosophical level, which are the components and motives that the designer relies on to develop the taste in designing women’s fabrics.